(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: People must develop a healthy lifestyle to have a longer and healthier life. Objective: to study the Public awareness toward healthy life of Iraqi community, and it relation with some of demographic variables. Method & persons: A cross-sectional study conducted from 20th June – 20th September 2022, through online questionnaire (google form) distributed through any available channels (e-mails, Viber, Chat, Messenger, WhatsApp, Telegram, Facebook groups) Results: Nine hundred and fifty-six Iraqi persons enrolled in this study, with age mean and standard deviation 32.67± 11.954; the highest percentage of participants 589(51.2%) aged ≤ 29 years, females 577(60.4%), currently married 480(50.2%), medical & health field worker 458(47.9%), while all the non- medical persons 498, (52.1%), students 212(22.2%), government non-medical worker 146(15.3%). most of the participants 812(84.9%) had once to twice brushing their teeth, and 408(42.7%) had sometimes using Dental floss, while 376(39.3%) of them never using dental floss, and only 39(41.1%)of the participant had regular teeth examination also good overall teeth health only in 387(40.5%). Acceptant-lifestyle 767(80.2%), and only 15(1.6%) had food & water intake poor lifestyle, while in overall-checkup the majority had poor overall-checkup 561(58.7%), then acceptable overall checkup 290(30.3%). Conclusion: Most of the participant had acceptance lifestyle in concerned food and water but had poor Overall checkup for vision, teeth, blood pressure, sugar, lipid and Regular doctor checkup in general.